1998
DOI: 10.1007/bf03190000
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of α2-adrenoceptor involvement in B[α]P induction processes of drug-metabolizing enzymes: the effect of stress

Abstract: Central to the appropriate regulation of behavioral and physiological changes induced by stress are the noradrenergic neuronal systems which have been implicated in a large number of stress-induced pathophysiological states. Endoplasmic reticulum-bound cytochromes (CYPs) play a crucial role in drug metabolism, resulting in deactivation or formation of reactive derivatives. In turn, these products may be responsible for the chemotherapeutic, mutagenic or carcinogenic properties of the parent compound. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
16
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
0
16
0
3
Order By: Relevance
“…Previous data have shown that catecholamines and adrenoceptors have been implicated in the modulation of hepatic enzymatic activities [12] (fig. 1).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous data have shown that catecholamines and adrenoceptors have been implicated in the modulation of hepatic enzymatic activities [12] (fig. 1).…”
mentioning
confidence: 99%
“…Previous studies have shown that psychological and physical stress is involved in the regulation of CYP1A1 and CYP1A2 [11][12][13][14]. In particular, repeated restraint stress, an experimental model of psychological and physical stress [15,16], has been found to modify both the constitutive and benzo( α )pyreneinduced CYP1A2-dependent 7-methoxyresorufin-O-dealkylase (MROD) activity [12,13].…”
mentioning
confidence: 99%
See 3 more Smart Citations